Plant Fructokinases: Evolutionary, Developmental, and Metabolic Aspects in Sink Tissues - Stein, Ofer; Granot, David (Frontiers in Plant Science, 2018)
Sucrose, a glucose–fructose disaccharide, is the main sugar transported in the phloem of most plants and is the origin of most of the organic matter. Upon arrival in sink tissues, the sucrose must be cleaved by invertase or sucrose synthase. Both sucrose-cleaving enzymes yield free fructose, which must be phosphorylated by either fructokinase (FRK) or hexokinase (HXK). The affinity of FRK to fructose is much higher than that of HXK, making FRKs central for fructose metabolism. An FRK gene family seems to exist in most, if not all plants and usually consists of several cytosolic FRKs and a single plastidic FRK. These genes are expressed mainly in sink tissues such as roots, stems, flowers, fruits, and seeds, with lower levels of expression often seen in leaves. Plant FRK enzymes vary in their biochemical properties such as affinity for fructose, inhibition by their substrate (i.e., fructose), and expression level in different tissues. This review describes recently revealed roles of plant FRKs in plant development, including the combined roles of the plastidic and cytosolic FRKs in vascular tissues and seed development.